I am C-3PO : the inside story - Daniels, Anthony (DK Publishing, 2019)
For the very first time, Daniels will tell C-3PO's story in its entirety, from seeing the first concept images to the early stages of the final film in the Skywalker saga, Star Wars: Episode IX, and in the process, will also tell his own.